Effect of Family Ownership, Corporate Social Responsibility, on Tax Avoidance: Moderating Effect of Audit Quality - Iskandar Itan; Natasya Artamevia (SEIKO : Journal of Management & Business, 2022)
Abstract Large tax collections are necessary for every nation's development and growth, but they are hampered by the reality that several people choose to avoid paying taxes in a number of different methods. This study is to investigate how audit quality, family ownership, and CSR affect tax avoidance. And also explores whether the causal relationship between tax avoidance and family ownership can be impacted by audit quality. Non-financial companies were used in this study. A total of 245 businesses registered on the Indonesia Stock Exchange (IDX) between 2017 and 2021 made up the sample that satisfied all requirements. The data were examined using panel regression. According to the results of regression analysis, tax avoidance and CSR are positively correlated, and companies that are unlikely to participate in tax avoidance are the companies that disclose their CSR activities well. Contrarily, family ownership negatively impacts tax avoidance, which leading family businesses to use tax avoidance more than non-family businesses. However, the relationship between family ownership and tax avoidance are unaffected by audit quality, which significantly positively impacts tax avoidance. Keywords: Tax Avoidance, Corporate Social Responsibility, family ownership, audit quality.